Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

What is the average rate of change of f(x) from x1=-10 to x2=-3? Please write your answer rounded to the nearest hundredth. f(x)= the square root of -9x+5

Sagot :

We have the following information

[tex]\begin{gathered} x_1=-10 \\ x_2=-3 \end{gathered}[/tex]

and the function

[tex]f(x)=\sqrt[]{-9x+5}[/tex]

In order to find the average rate, we need to find y1 and y2. Then, by substituting x1 into the function, we have

[tex]\begin{gathered} f(-10)=\sqrt[]{-9(-10)+5} \\ f(-10)=\sqrt[]{90+5} \\ f(-10)=\sqrt[]{95} \end{gathered}[/tex]

Similarly, by substituting x2, we get

[tex]\begin{gathered} f(-3)=\sqrt[]{-9(-3)+5} \\ f(-3)=\sqrt[]{27+5} \\ f(-3)=\sqrt[]{32} \end{gathered}[/tex]

Therefore, the average rate is given by

[tex]\frac{f(x_2)-f(x_1)}{x_2-x_1}=\frac{\sqrt[]{32}-\sqrt[]{95}}{-3-(-10)}[/tex]

which gives

[tex]\begin{gathered} \frac{f(x_2)-f(x_1)}{x_2-x_1}=\frac{\sqrt[]{32}-\sqrt[]{95}}{7} \\ \frac{f(x_2)-f(x_1)}{x_2-x_1}=\frac{5.6568-9.7467}{7} \\ \frac{f(x_2)-f(x_1)}{x_2-x_1}=-\frac{4.0899}{7} \end{gathered}[/tex]

Therefore, the average rate is

[tex]\frac{f(x_2)-f(x_1)}{x_2-x_1}=-0.58[/tex]

Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.